PENGARUH MODEL PEMBELAJARAN NUMBERED HEADS TOGETHER DAN TEAMWORK SKILL TERHADAP HASIL BELAJAR SISWA - Indah Pratiwi (Program Studi Pendidikan Guru Sekolah Dasar Universitas Nahdlatul Ulama Sumatera Utara, 2018)
This study aims to determine: (1) the better effect between students’ science learning outcomes that taught by numbered heads together (NHT) and direct instruction model, (2) a better effect between students’ science learning outcomes who have high teamwork skill and low teamwork skill, and (3) the interaction between learning model with teamwork skill in influencing learning outcomes. This research is quasi experimental. The sample in this research were selected by cluster random sampling of two classes. The instrument consists of tests of learning outcomes in the form of essay tests and pieces of observation tamwork skill observation. Data were analyzed using two way ANOVA. The results sho. The data were analyzed by using two-ways ANOVA. The result of this research showed that the students’ science learning outcomes by using numbered heads together model was different and showed a better results than direct instruction model, the students with the high teamwork skill showed better results than the students with the low teamwork skill, and there is an interaction between numbered heads together model and teamwork skill in influencing the students’ science learning outcomes.